Interaksi Sosial Pada Mahasiswi Bercadar di IAIN Palopo - Irzam; Ashabul Kahfi, Muhammad; Nuryani; Rahman, Saifur (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2022)
The veil as a social phenomenon that is currently in demand by students has an impact on student social interactions on campus. This study aims to determine the factors that encourage female students to wear the veil and to determine the pattern of social interaction carried out by veiled female students. This research is a qualitative research using data collection techniques in the form of observation, interviews, and documentation. The results showed that female students used the veil due to internal factors and external factors. Internal factors are the need for security and as an expression of religion. External factors are the social environment which is dominated by friends who are also veiled. Social interactions carried out by veiled female students produce associative social processes when interacting with fellow female students, and dissociative social processes when interacting with the opposite sex. Keywords: Veil, Interaction, Female Student